2017
DOI: 10.1093/biolre/iox028
|View full text |Cite
|
Sign up to set email alerts
|

The accessible chromatin landscape during conversion of human embryonic stem cells to trophoblast by bone morphogenetic protein 4†

Abstract: Human embryonic stem cells (hESCs) exposed to the growth factor bone morphogenetic protein 4 (BMP4) in the absence of FGF2 have been used as a model to study the development of placental development. However, little is known about the cis-regulatory mechanisms underlying this important process. In this study, we used the public available chromatin accessibility data of hESC H1 cells and BMP4-induced trophoblast (TB) cell lines to identify DNase I hypersensitive sites (DHSs) in the two cell lines, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Finally, when we compared ESCd to three commonly used placental cell lines: HTR-8/SVneo, BeWo, and JEG-3, we found that genes upregulated in ESCd were enriched for terms associated with cell invasion. These results provide strong evidence that after BAP treatment hESC differentiate into a subset of invasive placental cells, and may provide good model for studying TB functions, including invasion, as has been demonstrated in a number of other studies 40 44 .…”
Section: Discussionsupporting
confidence: 77%
“…Finally, when we compared ESCd to three commonly used placental cell lines: HTR-8/SVneo, BeWo, and JEG-3, we found that genes upregulated in ESCd were enriched for terms associated with cell invasion. These results provide strong evidence that after BAP treatment hESC differentiate into a subset of invasive placental cells, and may provide good model for studying TB functions, including invasion, as has been demonstrated in a number of other studies 40 44 .…”
Section: Discussionsupporting
confidence: 77%
“…Some key transcription factors (TFs) affecting differentiation have been identified, such as POU5F1, SOX2, and KLF4 (Nichols et al, 1998;Takahashi and Yamanaka, 2006;Goolam et al, 2016). Previously, our lab identified TFs for DNase I hypersensitive sites based on public available chromatin accessibility data of human embryonic stem cells (ESCs) and BMP4-induced trophoblast cell lines (Liu et al, 2017). The chromatin structure, including nucleosome positions, DNA methylation, and histone modifications also changed during the differentiation (Su et al, 2012;Xie et al, 2013;de Boni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since Xu et al proved that bone morphogenetic protein 4 (BMP4) could induce human ESCs, efficiently differentiating to trophoblast lineage, multiple research institutes have adopted this system as a model to study trophoblast lineage specification in vitro (Xu et al, 2002). Roberts's et al considered this model reliability by analyzing gene expression profiling through RNA sequencing (RNA-Seq) technology (Yabe et al, 2016;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a dataset from the Roadmap project, Liu et al [31] studied the DNase-seq landscape of BMP4-treated hESCs to identify cis-elements regulating early placental development. Though previously debated [32], recent evidence suggests that BMP4-treated hESCs represent early invasive trophoblast cells [33][34][35].…”
Section: Genome-wide Identification Of Enhancer Elements In the Humanmentioning
confidence: 99%